2014
DOI: 10.2174/1871529x14666140701095849
|View full text |Cite
|
Sign up to set email alerts
|

Alogliptin; A Review of a New Dipeptidyl Peptidase-4 (DPP-4) Inhibitor for the Treatment of Type 2 Diabetes Mellitus

Abstract: Dipeptidyl peptidase-4 inhibitors (DPP-4 inhibitors) are effective and safe oral incretin-based antihyperglycemic drugs. In preclinical studies, DPP-4 inhibitors have demonstrated cardiovascular benefits, independent of glycemic control, in patients with type-2 diabetes mellitus. Since 2005, various DPP-4 inhibitors (sitagliptin, linagliptin and saxagliptin) have been clinically available in the United States. Since 2013, alogliptin is the 4(th) approved DPP-4 inhibitor available on the market. Studies have sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 0 publications
1
7
0
Order By: Relevance
“…the base study appear to be generally comparable to those reported in studies of the presently marketed daily DPP-4 inhibitors (2)(3)(4)(5)(6). In the case of 2-h PMG, the incorporation of a study design in which the MTT was always performed at trough (day 7) supports the concept that the degree of DPP-4 inhibition observed at trough with the 25-mg dose is sufficient for maximal clinical efficacy.…”
Section: Discussionsupporting
confidence: 74%
“…the base study appear to be generally comparable to those reported in studies of the presently marketed daily DPP-4 inhibitors (2)(3)(4)(5)(6). In the case of 2-h PMG, the incorporation of a study design in which the MTT was always performed at trough (day 7) supports the concept that the degree of DPP-4 inhibition observed at trough with the 25-mg dose is sufficient for maximal clinical efficacy.…”
Section: Discussionsupporting
confidence: 74%
“…For detailed clinical pharmacology of alogliptin, please read recent reviews about this drug. 38,[41][42][43][44][45][46][47][48][49] Alogliptin as monotherapy or added to metformin, [50][51][52] pioglitazone, [53][54][55][56] glipizide, 57,58 glyburide/glibenclamide, 59 voglibose, [60][61][62] miglitol, 62 acarbose, 63 or insulin 64,65 significantly improves glycaemic control compared with placebo or active comparators in adult or elderly patients with inadequately controlled T2DM. This is associated with good gastrointestinal tolerability and a low incidence of hypoglycaemia.…”
Section: Dpp-4 Inhibitors In Diabetes Treatmentmentioning
confidence: 99%
“…This article aims to update our knowledge on the clinical pharmacology of alogliptin used for the treatment of T2DM, with a focus on clinical pharmacodynamics and pharmacokinetics, adverse effects, drug interactions and future directions. For detailed clinical pharmacology of alogliptin, please read recent reviews about this drug …”
Section: Introductionmentioning
confidence: 99%
“…For detailed clinical pharmacology of alogliptin, please read recent reviews about this drug. 19,[21][22][23][24][25][26][27][28][29]…”
Section: Introductionmentioning
confidence: 99%